Pengaruh Event Pariwisata dan Physical Evidence terhadap Keputusan Berkunjung - Ismail, Fahmiroellah Fariz; Iriani, Sri Setyo (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Indonesia is a maritime country, and it has more than thousands of beautiful islands. Those are the main reasons many domestic or even international tourists choose Indonesia for a holiday. White Sand Beach in Situbondo is one of the most visited tourist attractions. The local government that manages this place uses tourism events as a promotional medium and improves the physical evidence to attract more tourists to White Sand Beach for holidays. Therefore, this study aims to determine how effective tourism events and physical evidence influence the decision to visit this place. The survey was conducted using an online questionnaire and collected data from 50 early adult respondents who had visited the Beach. The data obtained were analyzed quantitatively through multiple linear regression analysis techniques in SPSS. This study shows that tourism events and physical evidence have a significant effect on visiting decisions. For further research, this study recommends comparing several different tourist attractions by adding variables and expanding the scope of respondents. The local government that manages the White Sand Beach tourism can use the findings as evaluation materials.